Prove that sin θ ( 1 – tan θ ) − cos θ ( 1 − cot θ ) = cosec θ − sec θ

Question

Prove that sin θ ( 1 – tan θ ) − cos θ ( 1 − cot θ ) = cosec θ − sec θ

in progress 0
Natalia 5 months 2021-07-08T02:19:08+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-08T02:20:30+00:00

    Step-by-step explanation:

    sinθ(1+tanθ)+cosθ(1+cotθ)

    =sinθ+

    cosθ

    sin

    2

    θ

    +cosθ+

    sinθ

    cos

    2

    θ

    =sinθ+

    sinθ

    cos

    2

    θ

    +

    cosθ

    sin

    2

    θ

    +cosθ

    A=

    sinθ

    sin

    2

    θ+cos

    2

    θ

    +

    cosθ

    sin

    2

    θ+cos

    2

    θ

    As,sin

    2

    θ+cos

    2

    θ=1

    A=

    sinθ

    1

    +

    cosθ

    1

    = cosecθ+secθ

Leave an answer

Browse

9:3-3+1x3-4:2 = ? ( )